Contemporary trends in psychological research on conspiracy beliefs. A systematic review - Pilch, Irena; Turska-Kawa, Agnieszka; Wardawy, Paulina; Olszanecka-Marmola, Agata; Smołkowska-Jędo, Wiktoria (Frontiers in Psychology, 2023)
Background The number of psychological studies on conspiracy beliefs has been systematically growing for about a dozen years, but in recent years, the trend has intensified. We provided a review covering the psychological literature on conspiracy beliefs from 2018–2021. Halfway through this period, the COVID-19 pandemic broke out, accompanied by an explosion of movements based on conspiracy theories, intensifying researchers’ interest in this issue. Methods Adhering to PRISMA guidelines, the review systematically searched for relevant journal articles published between 2018-2021. A search was done on Scopus and Web of Science (only peer-reviewed journals). A study was included if it contained primary empirical data, if specific or general conspiracy belief(s) were measured and if its correlation with at least one other psychological variable was reported.All the studies were grouped for the descriptive analysis according to the methodology used, the participants’ characteristics, the continent of origin, the sample size, and the conspiracy beliefs measurement tools. Due to substantial methodological heterogeneity of the studies, narrative synthesis was performed. The five researchers were assigned specific roles at each stage of the analysis to ensure the highest quality of the research. Results Following the proposed methodology, 308 full-text articles were assessed for eligibility and 274 articles (417 studies) meeting the inclusion criteria were identified and included in the review. Almost half of the studies (49.6%) were conducted in European countries. The vast majority of the studies (85.7%) were carried out on samples of adult respondents. The research presents antecedents as well as (potential) consequences of conspiracy beliefs. We grouped the antecedents of conspiracy beliefs into six categories: cognitive (e.g., thinking style) motivational (e.g., uncertainty avoidance), personality (e.g., collective narcissism), psychopathology (e.g., Dark Triad traits), political (e.g., ideological orientation), and sociocultural factors (e.g., collectivism). Conclusions and Limitations The research presents evidence on the links between conspiracy beliefs and a range of attitudes and behaviors considered unfavorable from the point of view of individuals and of the society at large. It turned out that different constructs of conspiracy thinking interact with each other. The limitations of the study are discussed in the last part of the article.